Efficacy of cyclosporine eyedrop 0.1% in the treatment of dry eye in primary sjogren's syndrome: A prospective Indian study - Swapnali Sabhapandit; Madhuri Radhakrishna; Shireesha Anumula; Arifa Shaik; Solomon Perumalla; Sahithi Venapally (Indian Journal of Rheumatology)
Objectives: The objective of this study was to evaluate the efficacy and safety of 0.1% cyclosporine A (CsA) eyedrop in patients having primary Sjogren's syndrome (SS) in India. Methods: A prospective consecutive case series of total 20 patients with moderate-to-severe dry eyes were treated with 0.1% CsA eyedrop twice daily along with lubricating eyedrop for 3 months. Efficacy measures included ocular staining score (OSS), van Bijsterveld score (VBS), and Schirmer's score of each eye based on the 2016 ACR-EULAR classification. Subjective improvement was also recorded at the final visit. Any adverse effects were noted. Results: Treatment with 0.1% CsA eyedrop showed a statistically significant improvement at 3 months for both OSS and VBS in each eye of study patients. A similar improvement in Schirmer's score was noted in each eye of the subjects. Subjective improvement of ocular sicca symptoms was also demonstrated. There was excellent compliance to therapy. The 0.1% CsA formulation did not show any topical or systemic side effects in any patient. Conclusion: The 0.1% ophthalmic preparation of CsA is safe and effective in the management of moderate-to-severe dry eyes in patients with primary SS in this pilot study in Indian patients.